Organization of Petroleum Exporting Countries: facts, figures and analysis (Frankfort, Germany Deutsche Bank, 1975)
The aim and purpose of this brochure is also to describe the developments in the individual OPEC countries and to contribute to the strengthening of cooperation between the oil-producing countries and the Federal Republic of Germany
osc 27/08/2021
Loans
Keywords: OPEC; Oil export; Oil industry